Re-analyzing and confirming a differential use of redintegration in students with mild and borderline intellectual disabilities - Bruns, Gunnar (Frontiers in Psychology, 2024)
While numerous studies on verbal working memory have investigated the capacity of the phonological loop and the effectiveness of rehearsal as one core process for maintaining the memory trace, the reconstruction of the memory trace from long-term memory, called redintegration, has been studied less thoroughly. This holds particularly for the population of students with special educational learning needs and mild and borderline intellectual disabilities (MBID). In a previous study, we found a differential developmental relation between the effectiveness of redintegration and vocabulary size (Bruns et al., 2019), counter-intuitively suggesting that students with MBID tend to show less effective redintegration with higher vocabulary size. However, differential item functioning (DIF) in the picture naming task may have biased the result. Therefore, the current study is a re-analysis of this interaction controlling for DIF in the vocabulary measure. To this end, the items of the picture naming task (k = 95) were analyzed through a Rasch model, and k = 29 biased items were excluded. The resulting corrected vocabulary score was used to predict the redintegration effectiveness, comparing students with and without MBID. The interaction remains significant, supporting the original finding that students with MBID have a differential developmental pattern and are less able to make adequate use of a growing vocabulary when reconstructing traces in their working memory. Implications of this result for the understanding of MBID and further research directions are discussed.